A comparison between the effects of shape memory alloys and carbon nanotubes on the thermal buckling of laminated composite beams. Issue 7 (3rd July 2022) - Kamarian, Saeed; Bodaghi, Mahdi; Isfahani, Reza Barbaz; Song, Jung-il
Abstract: One of the essentials for designing composite structures exposed to heat is the correct choice of reinforcing materials. In the present research work, a comparison is made between the performances of two well-known advanced materials, Shape Memory Alloys (SMAs) and Carbon Nanotubes (CNTs), in thermal bucking behavior of thin composite beams with simply supported boundary conditions. First, the effect of embedding SMA wires on the thermal buckling of laminated composite beams are examined. The stability equations are derived based on Timoshenko Beam Theory (TBT), and the critical buckling temperatures are obtained analytically. The advantages and disadvantages of using SMA wires as well as their proper functional range are studied. Then, in the next step, the influence of CNTs on the thermal buckling response of composite beams is presented. To this end, the results of some experiments such as Dynamic Mechanical Thermal Analysis (DMTA) and Thermo-Mechanical Analysis (TMA) tests are used to obtain thermal properties of CNT-reinforced composite materials. The performance of CNTs is also evaluated in comparison with SMA wires. It is found from the analysis that, depending on the structural conditions, one reinforcing material can outperform the other. Finally, the idea of simultaneous use of both reinforcing materials comes up. The results show that, in some circumstances, the use of only one of the SMAs or CNTs does not have significant effect on the thermal buckling of composite beams, but applying both of these advanced reinforcing materials in the composite medium can extraordinarily enhance the critical buckling temperatures.